Aspects of the syntax of prepositions and prepositional phrases in English and Polish - Jaworska, E; Jaworska, Ewa (1987)
﻿ The present thesis focusses on the structure of PP's in English and Polish, and the occurrence of PP's in subject and object positions. The main theoretical references are the X-bar Theory of syntactic categories and the Government Binding framework (GB). A consideration of English data corroborates Jackendoff's and Emonds' claim that apart from an NP, prepositions can take a PP and an S′ complement or no complement at all, though details of Jackendoff's analysis are revised. Polish prepositions allow the same range of complements, including no complement, although,with a greater variety of complex prepositions and with intransitive prepositions modified by relative and appositive clauses, the P-PP and the P-S′ structures are less common in Polish than in English. Subject and object PP's have so far received little attention. Like PP objects of prepositions, they are used if the intended meaning cannot be expressed by a suitable NP. The appearance of subject PP's in raising and passive sentences poses a problem for classical Transformational Grammar, though not for a slightly revised version of GB – another category-based framework. The analysis proposed here involves a particular view of the representation of Case, and a revised Case Filter. The Case Filter rules out not merely any lexical NP with no Case but any lexical XP which requires Case but has not been assigned Case. Thus, the properties of being an NP and requiring Case are independent of each other. It emerges from the investigation (i) that prepositions in English and Polish are more alike than one might expect, given the obvious differences between the two languages; (ii) that prepositions and PP's are like verbs and VP's – as Jackendoff emphasizes – but in some respects they show greater resemblance to other categories; and (iii) that syntactic categories are less important for the distribution of phrases than is commonly assumed, and that the meaning of phrases is of central importance for their distribution.